PENGARUH GAYA KEPEMIMPINAN, KARAKTERISTIK PEKERJAAN DAN KEPUASAN KERJA TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT MITRA SEJATI MEDAN - Giawa, Yolanda Tesania; Tinambunan, Anitha Paulina (Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine the effect of leadership style, job characteristics and job satisfaction on the performance of nurses at Mitra Sejati Hospital Medan. Data were obtained directly from respondents (nurses) at Mitra Sejati Hospital Medan. The total population of this study was 82 people and the number of samples through the census was 82 people. The analysis technique used in this research is multiple linear regression, descriptive analysis and hypothesis testing. The results of this study indicate that the variables of leadership style, job characteristics and job satisfaction simultaneously (simultaneously) have a positive and significant effect on the performance of nurses at Mitra Sejati Hospital Medan. While partially shows that leadership style has a positive and significant effect on the performance of nurses at Mitra Sejati Hospital Medan with a regression coefficient value of 0.232 and a significance value of 0.001 <= 0.05 (smaller than the error tolerance value). Job characteristics have a positive and significant effect on the performance of nurses at Mitra Sejati Hospital Medan with a regression coefficient value of 0.321 and a significance value of  0.000 0.05 (smaller than the error tolerance value). Job satisfaction has a positive and significant effect on the performance of nurses at Mitra Sejati Hospital Medan with a regression coefficient value of 0.267 and a significance value of 0.013 <=0.05 (greater than the error tolerance value).